EXTRACTION, PURIFICATION AND CHARACTERIZATION OF LIPOXYGENASE FROM CONOPHOR NUT (Tetracarpidium conophorum) - Oguntoyinbo, Oladotun O.; Abiodun, Abayomi Malomo; Adebayo, Oludare David; Enujiugha, Victor N. (FUDMA JOURNAL OF SCIENCES, 2023)
Lipoxygenase (LOX) is an enzyme that catalyses the step-wise oxygenation of polyunsaturated fatty acids (PUFAs) to form fatty acid hydroperoxides within living tissues. In the present study, lipoxygenase was isolated from defatted and whole (full fat) conophor nut (Tetracarpidium conophorum) and purified to homogeneity using 60% ammonium sulphate precipitation, DEAE-sephadex A50 and sephadex G-200 chromatography. The effects of pH and temperature on the activity and stability of LOX were investigated. The optimum pH and temperature of the purified lipoxygenase were 5.0 and 50 oC, respectively. Lipoxygenase activity was stable at 40 oC and 50 oC after an hour of incubation. The enzyme was stable at pH values of 5.0 and 6.0. The activity of the enzyme was enhanced by Ca2+ while Zn2+, Fe2+ and Cu2+ inhibited its activity. The Km and Vmax values were 40.38 µM and 125 µmol/min/mg proteins, respectively. The molecular weight was estimated to be 67.83 kDa by SDS-PAGE. The findings reveal that conophor nut can be a cheap source of industrial lipoxygenase, which could be exploited in various biotechnological applications. The enzyme’s thermostability and adaptation in slightly acidic medium are factors that can help boost its acceptability in food systems.